STEPS AND STRATEGIC FACTORS FOR CAREER DEVELOPMENT IN HUMAN RESOURCES BASED ON THE INDONESIAN NATIONAL QUALIFICATIONS FRAMEWORK - Maulan, Farhan; Handayani, Ni Putu Lidia; Supratikta, Hadi (Universitas Muhammadiyah Metro, 2025)
Human resources (HR) play an important role in organizational performance. Career planning and development is an efficient way to improve the quality of human resources. This research aims to develop HR career development steps based on the Indonesian National Qualifications Framework. This research method is qualitative, with an in-depth approach to the phenomenon. Data analysis was carried out using a qualitative approach, producing descriptive information from the participants observed. Even though the action learning method is used in leadership training design, the training material has not yet achieved the target of developing individual behavior. Training evaluation is carried out using pre-test, post-test and questionnaires to see changes in employee behavior after training